2018
DOI: 10.1089/scd.2017.0200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Wnt/β-Catenin Pathway by an Inflammatory Microenvironment Affects the Myogenic Differentiation Capacity of Human Laryngeal Mucosa Mesenchymal Stromal Cells

Abstract: Various microenvironments influence the multiple differentiation potential of mesenchymal stromal cells. For example, inflammatory microenvironment can suppress the myogenic differentiation capability of laryngeal mucosa mesenchymal stromal cells (LM-MSCs). The present study therefore sought to identify the underlying molecular mechanisms regulating these processes. We isolated a novel population of MSCs, LM-MSCs, from the laryngeal mucosa tissues. The cells were cultured in osteogenic, adipogenic, and myogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Separate microenvironments reflect multiple differentiation potentials involving mesenchymal stromal cells. For example, an inflammatory microenvironment suppresses myogenic differentiation capability regarding laryngeal mucosa mesenchymal stromal cells [LM‐MSCs] (Yang et al, 2018 ). In the current study, we also found that inflammatory cytokines (TNF‐α and IL‐1β) in MG patients were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Separate microenvironments reflect multiple differentiation potentials involving mesenchymal stromal cells. For example, an inflammatory microenvironment suppresses myogenic differentiation capability regarding laryngeal mucosa mesenchymal stromal cells [LM‐MSCs] (Yang et al, 2018 ). In the current study, we also found that inflammatory cytokines (TNF‐α and IL‐1β) in MG patients were increased.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐20b, miR‐296, and Let‐7f have been shown to be involved in the regulation of the WNT signaling pathway and angiogenesis by regulating multiple TGs belonging to these pathways . Specifically, PPP2R1B, MYC, and TNF are known to be key regulators of the WNT signaling pathway and HIF1A, while VEGFA and STAT3 are described as key regulators of angiogenesis and the VEGF signaling pathway . MPP3 is known to play a pivotal role in extracellular matrix restructuring of epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL-1β expression levels are significantly higher in OA than in healthy sites and is associated with subchondral destruction 14 . Mechanistically, the inhibitory effects of IL-1β have been associated with MSCs proliferation and the activation of osteoclastogenesis 15 , 16 . IL-1β treatment can also dramatically induce the production of ROS, nitric oxide (NO), and proteolytic enzymes such as matrix metalloproteinase (MMP) during bone formation, thus inhibits BMSCs osteogenic differentiation and bone tissue generation in vitro and in vivo 17 19 .…”
Section: Introductionmentioning
confidence: 99%